Virtual reality helps San Diego to compete. - Murray, T. J. (Public Management (00333611), 1995)
Virtual reality (VR) has helped the city of San Diego, California, to compete as a prime venue for a national-level convention. The city's data-processing arm developed a three-dimensional (3D) model of the convention center that was to be used as a VR walk-through in the city's bid to hold the 1996 Republican National Convention. When it was completed, the real value of the virtual convention center resulted from the direct, interactive means of problem resolution that it provided, in particular for the technical staff members of the site selection committee for the Republican convention. These experts were able to anticipate problems, discuss issues, and develop solutions using the VR model. Although VR and 3D modeling did allow San Diego to successfully bid for the convention, the most productive use of the process will be in the areas of land use, land reuse, and events re-creation.